OCTOPOD: single-bunch tomography for angular-spectral characterization of laser-driven protons - M. Reimold; S. Assenbaum; E. Beyreuther; E. Bodenstein; F.-E. Brack; C. Eisenmann; F. Englbrecht; F. Kroll; F. Lindner; U. Masood; J. Pawelke; U. Schramm; et al. (High Power Laser Science and Engineering, 2023)
Laser–plasma accelerated (LPA) proton bunches are now applied for research fields ranging from ultra-high-dose-rate radiobiology to material science. Yet, the capabilities to characterize the spectrally and angularly broad LPA bunches lag behind the rapidly evolving applications. The OCTOPOD translates the angularly resolved spectral characterization of LPA proton bunches into the spatially resolved detection of the volumetric dose distribution deposited in a liquid scintillator. Up to 24 multi-pinhole arrays record projections of the scintillation light distribution and allow for tomographic reconstruction of the volumetric dose deposition pattern, from which proton spectra may be retrieved. Applying the OCTOPOD at a cyclotron, we show the reliable retrieval of various spatial dose deposition patterns and detector sensitivity over a broad dose range. Moreover, the OCTOPOD was installed at an LPA proton source, providing real-time data on proton acceleration performance and attesting the system optimal performance in the harsh laser–plasma environment.